ТЕХНІКО-ЕКОНОМІЧНЕ ОБГРУНТУВАННЯ ДОЦІЛЬНОСТІ РЕКОНСТРУКЦІЇ ТРИФАЗНОЇ ДУГОВОЇ СТАЛЕВАРНОЇ ЕЛЕКТРОПЕЧІ - Гудим, В.І.; Косовська, В.В.; Яворська, Н.П.; Данько, Т.І. (Інститут електродинаміки НАН України, Київ, 2021)
The technological units of electric arc steel remelting are among the most energy-intensive consumers for whom the problem of energy saving is extremely urgent. The proposed reconstruction of the electric-arc steel furnace is aimed at reducing the amount of electricity consumption. The feasibility study makes it possible to assess the technical and economic parameters of project of an electric-arc steel furnace reconstruction. The simulation results of the reconstructed electric furnace showed that due to the optimal placement of electric arcs in the electric furnace space, the duration of the metal melting stage can be reduced by approximately 19 min. Cost-effectiveness calculations for the implementation of the innovative solution showed that reducing the duration of steel remelting in a reconstructed furnace reduces the electricity consumption by approximately 28% per process. The article takes into account only the reduction of electricity consumption, but does not take into account the possibility of improving the productivity of the furnace by increasing the number of technological processes per shift. References 7, figures 3, table 1.